Success in manufacturing employment in an industrial district: Higher productivity or lower wages? - Charlie Karlsson; Johan Klaesson (European Regional Science Association (ERSA), 1998)
The south-western part of the county of Jonkoping in Sweden has an industrial structure that is very different from that in the rest of Sweden. The region which may be characterised as an ?industrial district?, is dominated by small and medium-sized enterprises. It is well-known for its entrepreneurial spirit and in the international literature it has been compared with other entrepreneurial regions, such as ?the third Italy?, Rhone-Alps, Baden-Wurttemberg, and Silicon Valley. The employment share for manufacturing in the region is approximately double that of the rest of Sweden. This pattern seems to be very stable over time. Industries which are declining in other parts of Sweden are actually expanding in this region. The purpose of the current paper is to try to explain why the manufacturing industry is so successful in this region. In the paper we test a number of different hypotheses. In particular, we investigate whether the apparent success is the result of higher productivity growth or if it is the result of low input costs, mainly low wages. Differences in productivity growth or in input costs might be the result of the existence of particular types of agglomeration economies. In the paper we investigate the role of such economies. In the analysis we use productivity and gross profit distributions of Salter type. These distributions we estimate by using data on sales value, value added and wages for the manufacturing industry in Sweden for various years collected by Statistics Sweden.
Keywords: 330